Study on Teachers’ Behavior and Participation in Developing the Teaching Lao Language for Communication for Teachers in Phonethong District, Luang Prabang Province, Academic Year 2019-2020 - INVANKHAM, Maiphone; CHANHTHAHONG, Khamxay; NIMNUAN, Laion; PATHOUMVHANH, Phanthamanath; INTHAVONG, Veinganousouk (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)